MOVE STRUCTURE OF INTRODUCTIONS IN THE FINAL REPORTS WRITTEN BY THE STUDENTS OF ENGLISH DEPARTMENT AT SRIWIJAYA STATE POLYTECHNIC - Muhammad Nadjmuddin (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2013)
The objectives of the study are to identify rhetorical functions in the Introduction Chapter ofFinal Report and to examine whether rhetorical functions utilized by the students of EnglishDepartment at Sriwijaya State Polytechnic have or have not fulfilled the rhetorical structure proposed inSwales‟ move model. The corpus was collected through purposive random sampling from a number offinal reports written by the students. The study used Swales‟ move model in analyzing the corpus. Theresults indicate that, despite similarities with Swales‟ move model, there are some differences betweenthe students‟ introductions and the model. It is assumed that the different features of the rhetoricalstructures are influenced by specific characteristics of the polytechnic final reports and their academicwriting capacity. Most of the introductions have not met the criteria or principles as suggested inSwales‟ move. This study shows that there is a need to teach the principles of scientific writing to thestudents and increase their awareness of rhetorical structure of academic genre. The study has shownthat Swales‟ model is useful framework in analyzing students‟ final report introductions, but otherstudies are necessary to compare and reveal their specific characteristics in different disciplines.